2009
DOI: 10.1245/s10434-009-0507-4
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Loss of Fragile Gene Expression in Pancreatobiliary Cancers: Correlations Among Markers and Clinical Features

Abstract: Background Loss of expression of fragile gene products, Fhit and Wwox, occurs in many cancer types, with loss exhibited early in the neoplastic process in some. Wwox has been understudied in pancreatobiliary cancers, especially in relation to other involved tumor suppressors. We have assessed the status of the Fhit and Wwox proteins encoded by DNA damage susceptible chromosome fragile sites encompassed by FHIT and WWOX tumor suppressor genes. Methods Pancreatic, gallbladder and ampullary cancers, normal panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Guler, et al demonstrated coordinate absence or reduction of FHIT and WWOX expression in 55 and 63% of invasive breast tumors was reported (Guler et al, 2004). Coordinate loss of FHIT and WWOX has also been reported in other tumors (Dumon et al, 2001;Guler et al, 2004;Bloomston et al, 2009). These investigators provided some evidence for our study to a certain extent.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Guler, et al demonstrated coordinate absence or reduction of FHIT and WWOX expression in 55 and 63% of invasive breast tumors was reported (Guler et al, 2004). Coordinate loss of FHIT and WWOX has also been reported in other tumors (Dumon et al, 2001;Guler et al, 2004;Bloomston et al, 2009). These investigators provided some evidence for our study to a certain extent.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, several mechanisms such as deletions, point mutations, methylation, loss of a whole chromosome and genetic recombination contributed to loss of FHIT and WWOX expression, we did not explore deeply on the mechanisms. However, some evidence demonstrated that loss of FHIT and WWOX expression was proportionally more frequent than abnormalities in p53, p16, or SMAD4 expression (Bloomston et al, 2009). It is well-known that aberrant p53 expression which happens at early event in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fhit staining intensity in our patients had a strong association with smoking and non-vegetarian dietary intakes, thereby re-confirming the previous hypothesis of epigenetic factors in deletions and dysregulation in Fhit gene, as in lung cancer development [16][17][18][19]21,22,24,48] . Many of our carcinoma cases were negative for Fhit protein although expression for the protein was retained by a couple of cases which could be the result of a dysregulated gene that have been observed in other tumors, including lungs and breast [20,21,24,33,43,48] . Our observation in the normal control was similar to Hao et al [30] where they documented cytoplasmic expression in normal colonic epithelial cells from basal onwards to luminal differentiated cells.…”
Section: Discussionmentioning
confidence: 98%
“…The affected crypt thereby undergoes fission to give rise to an early flat lesion like ACF [6,38] . Similarly to our observations, gradual reductions in the intensity of Fhit protein had been reported by other groups in colon cancer and its early precursor lesions, and also in other pre-neoplastic lesions in breast, pan- T1 T2 T3 T4 N0 N1 N2 M0 M1 Total Negative 9 3 12 12 12 Weak 3 14 1 10 8 18 18 Moderate 16 2 8 7 3 15 3 18 Strong 24 3 27 0 27 27 Total 3 63 9 57 15 3 72 3 75 creas, cervix, lung and esophagus [15][16][17][18]20,21,[25][26][27][28][29][30][31]33,43,44] . Functional loss of the tumor suppressor protein Fhit, like p53, is believed to result in loss of inhibitory function in cell proliferation due to release phenomena in many downstream proteins acting on cell proliferations [16][17][18][19]45] .…”
Section: Discussionmentioning
confidence: 99%
“…WWOX gene spans more than a million base pairs and is thus prone to many chromosomal rearrangements observed in different cancers [22][23][24]. The loss or reduced expression of WWOX was found in various cancer [25][26][27]. However, whether the alterative expression of WWOX has the effect to immune system has not been studied.…”
Section: Introductionmentioning
confidence: 99%